The Interaction Between Gastronomy and Law: A Regulatory Study of Culinary Practices in Kuningan, West Java - Utami, Nadya Rechtta (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2025)
This research examines the interaction between gastronomy and law through a regulative approach to culinary practices in Kuningan Regency, West Java, Indonesia. The region is known for its diverse traditional culinary treasures and is an important part of the local cultural identity. However, the development of the culinary sector cannot be separated from the influence of various legal regulations, both formal ones such as business licensing, halal certification, and food safety standards, as well as informal social norms that live in the community. The research method used is a qualitative approach with field study methods, in-depth interviews with local culinary business actors, and normative analysis of regional regulations and national policies related to food and intangible cultural heritage. This research also examines the dynamics between traditional culinary practices and modern legal demands. The results show that there is a tension between local culinary preservation efforts and the need to fulfill formal legal requirements, such as distribution permits and certification. Many small businesses experience administrative barriers and additional costs in meeting these requirements. On the other hand, there is great potential for the law to play a role in the protection and promotion of traditional cuisine if integrated with cultural and tourism policies. In conclusion, the interaction between gastronomy and law in Kuningan reflects the importance of harmonization between the regulatory framework and socio-cultural dynamics. A more inclusive and contextual legal approach is needed to support the sustainability of local culinary as part of the national cultural heritage.